Initial treatment of steroid-sensitive idiopathic nephrotic syndrome in children with mycophenolate mofetil versus prednisone: protocol for a randomised, controlled, multicentre trial (INTENT study). Issue 10 (10th October 2018) - Ehren, Rasmus; Benz, Marcus R; Doetsch, Jorg; Fichtner, Alexander; Gellermann, Jutta; Haffner, Dieter; Höcker, Britta; Hoyer, Peter F; Kästner, Bärbel; Kemper, Markus J; Konrad, Martin; Luntz, Steffen; et al.
Abstract : Introduction: Idiopathic nephrotic syndrome is the most common glomerular disease in childhood with an incidence of 1.8 cases per 100 000 children in Germany. The treatment of the first episode implies two aspects: induction of remission and sustainment of remission. The recent Kidney Disease Improving Global Outcomes, American Academy of Pediatrics and German guidelines for the initial treatment of the first episode of a nephrotic syndrome recommend a 12-week course of prednisone. Despite being effective, this treatment is associated with pronounced glucocorticoid-associated toxicity due to high-dose prednisone administration over a prolonged period of time. The aim of the INTENT study (Initial treatment of steroid-sensitive idiopathic nephrotic syndrom in children with mycophenolate mofetil versus prednisone: protocol for a randomised, controlled, multicentre trial) is to show that an alternative treatment regimen with mycophenolic acid is not inferior regarding sustainment of remission, but with lower toxicity compared with treatment with glucocorticoids only. Methods and design: The study is designed as an open, randomised, controlled, multicentre trial. 340 children with a first episode of steroid-sensitive nephrotic syndrome and who achieved remission by a standard prednisone regimen will be enrolled in the trial and randomised to one of two treatment arms. The standard care group will be treated with prednisone for a total of 12 weeks; in the experimental group the treatment is switched to mycophenolate mofetil, also for a total of 12 weeks in treatment duration. The primary endpoint is the occurrence of a treated relapse within 24 months after completion of initial treatment. Ethics and dissemination: Ethics approval for this trial was granted by the ethics committee of the Medical Faculty of the University of Heidelberg (AFmu-554/2014). The study results will be published in accordance with the Consolidated Standards of Reporting Trials statement and the Standard Protocol Items: Recommendations for Interventional Trials guidelines. Our findings will be submitted to major international paediatric nephrology and general paediatric conferences and submitted for publication in a peer-reviewed, open-access journal. Trial registration number: DRKS0006547; EudraCT2014-001991-76; Pre-result. Date of registration: 30 October 2014; 24 February 2017.